Projecting the Mental Model of Social Networking Site Usage - Wu, Chun-Hui; Yan, Yih-Her; Shu, Kuen-Ming (Advances in Technology Innovation, 2017)
The growth of online social networking sites (SNS) has created a new world of connection and communication for online users. SNS usage has become an important part of people’s daily lives. This study aims to obtain new insights towards SNS usage behaviour. Based on participants’ mental models, it is hoped to make more clear exposition about their perceptions and experiences as well as to explore what factors affect their behaviour for using social networking sites. A blend of qualitative methodologies was adopted for data collection and analysis, including the Zaltman metaphor elicitation technique (ZMET) method, the laddering technique, and the means-end chain theory. The results of this study show that the most important values of using SNS include its convenience, maintaining relationship, gaining relaxation, as well as reaching coherence. Additionally, participants pointed out they cared about their online privacy issues very much and had found some potential dangers; however, they continued to use these sites because of the great benefits and enjoyment.